Association of baseline knee sagittal dynamic joint stiffness during gait and 2-year patellofemoral cartilage damage worsening in knee osteoarthritis. Issue 2 (February 2017) - Chang, A.H.; Chmiel, J.S.; Almagor, O.; Guermazi, A.; Prasad, P.V.; Moisio, K.C.; Belisle, L.; Zhang, Y.; Hayes, K.; Sharma, L.
Summary: Objective: Knee sagittal dynamic joint stiffness (DJS) describes the biomechanical interaction between change in external knee flexion moment and flexion angular excursion during gait. In theory, greater DJS may particularly stress the patellofemoral (PF) compartment and thereby contribute to PF osteoarthritis (OA) worsening. We hypothesized that greater baseline knee sagittal DJS is associated with PF cartilage damage worsening 2 years later. Methods: Participants all had OA in at least one knee. Knee kinematics and kinetics during gait were recorded using motion capture systems and force plates. Knee sagittal DJS was computed as the slope of the linear regression line for knee flexion moments vs angles during the loading response phase. Knee magnetic resonance imaging (MRI) scans were obtained at baseline and 2 years later. We assessed the association between baseline DJS and baseline-to-2-year PF cartilage damage worsening using logistic regression with generalized estimating equations (GEE). Results: Our sample had 391 knees (204 persons): mean age 64.2 years (SD 10.0); body mass index (BMI) 28.4 kg/m 2 (5.7); 76.5% women. Baseline knee sagittal DJS was associated with baseline-to-2-year cartilage damage worsening in the lateral (OR = 5.35, 95% CI: 2.37–12.05) and any PF (OR = 2.99, 95% CI: 1.27–7.04) compartment. Individual components of baseline DJS (i.e., change in knee moment or angle) were not associated with subsequent PF disease worsening. Conclusion: Capturing the concomitant effect of knee kinetics and kinematics during gait, knee sagittal DJS is a potentially modifiable risk factor for PF disease worsening.